Hubungan Tingkat Pengetahuan dengan Kepatuhan Hand Hygiene di Puskesmas Ciparay DTP - Willyana Syafriyanti; Yana Afrina; Ahmad Zaelani; Mungki Octavia; Heru Badrussalam (Universitas Muhammadiyah Manado, 2026)
Nosocomial infections, or Healthcare-Associated Infections (HAIs), are infections acquired by patients during treatment in hospitals or other healthcare facilities. Hand hygiene is an important effort in preventing nosocomial infections, but its practice remains low. Many factors influence hand hygiene compliance among healthcare workers, one of which is knowledge level. This study aims to analyze the relationship between knowledge level and hand hygiene compliance among workers at the Ciparay DTP Public Health Center. The instruments used in this study were a knowledge level questionnaire and a hand hygiene compliance questionnaire. The research method used was quantitative with a cross-sectional approach. The sample used in this study was 71 people. Data analysis was performed using the Fisher's Exact test. The results showed that the majority of respondents were male (62%), aged 36.6% between 31 and 40 years, and had a maximum length of service of <5 years (39.4%). The majority of respondents (93%) were compliant with hand hygiene practices, and the majority (84.5%) had good knowledge. Bivariate analysis showed a significant relationship between knowledge level and hand hygiene compliance among workers at the Ciparay DTP Public Health Center, with a p-value of <0.005. Knowledge level is a crucial factor in the implementation of hand hygiene in Public Health Center. Continuous education for Public Health Center workers can be an effort to encourage hand hygiene compliance in Public Health Center, thereby preventing nosocomial infections in Public Health Center.